2000
DOI: 10.1177/004051750007000602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Peracetic Acid Bleaching of Cotton as an Environmentally Safe Alternative to Hypochlorite Bleaching

Abstract: Peracetic acid is produced directly in the bleaching liquor from acetic anhydride and hydrogen peroxide. The acid can be catalyzed to bleach knitted cotton fabric at temper atures as low as 30°C in the presence of 2.2' bipyridine, sodium lauryl sulfate, and sodium tetraborate. We evaluate the effects of the concentrations of hydrogen peroxide and acetic anhydride as well as treatment temperature, time, and pH on whiteness, bursting strength, and water absorbency of the fabric. The results of our investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Results of whiteness index (WI) (Table 2) reveal that, optimal WI values are achieved at pH 8; blow or above pH 8 lower WI values are observed irrespective of the substrate used. The results are in full conformation with previous reports which ascribed this to liberation of perhydroxyl anions which are mainly responsible for bleaching, can only occur in neutral and alkaline medium (Guersoy & Dayioglu, 2000;Hashem, 1999;). pH's higher than pH 8 decrease the values of whiteness index.…”
Section: Ph Of Bleaching Mediumsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of whiteness index (WI) (Table 2) reveal that, optimal WI values are achieved at pH 8; blow or above pH 8 lower WI values are observed irrespective of the substrate used. The results are in full conformation with previous reports which ascribed this to liberation of perhydroxyl anions which are mainly responsible for bleaching, can only occur in neutral and alkaline medium (Guersoy & Dayioglu, 2000;Hashem, 1999;). pH's higher than pH 8 decrease the values of whiteness index.…”
Section: Ph Of Bleaching Mediumsupporting
confidence: 91%
“…An important advantage of peracetic acid, which contain -COOH groups, is that they are fast acting, non foaming, water soluble liquids and break down to innocuous decomposition products that are environmentally acceptable (Guersoy & Dayioglu, 2000;Hashem, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Bleaching with peracetic acid (PAA) is an alternative to bleaching with HP [27][28][29][30][31][32][33][34]. It is a powerful oxidizing agent (redox potential: 1.81 eV) [35] with excellent antimicrobial and bleaching properties.…”
mentioning
confidence: 99%
“…Distilled water was used in preparing all chemicals. Peracetic acid was produced directly in the bleaching liquor, and 7 g of fabric was used for bleaching at a liquor ratio of 1/143 [3]. In this study, we conducted experiments using, first, a two-level full factorial experimental design, which included three levels of each variable (-1, 0, + 1 ), and then a central composite experimental design, which included five levels of each variable (-a, -1, 0, + 1, +a) [2].…”
mentioning
confidence: 99%
“…The other process parameters-75 ml of a 1 % (m/v) solution of sodium lauryl sulfate, 90 ml of a 2 gll solution of 2.2' bipyridine, and 500 ml of a 17.5 g/1 solution of sodium tetraborate in 1000 ml of bleaching liquor-were kept constant. We fixed the limits for the process variables based on our previous study [3], as shown in Table I. Base levels of the variables were represented in coded form by -1, 0, + 1.…”
mentioning
confidence: 99%